2021
DOI: 10.2147/jir.s328334
|View full text |Cite
|
Sign up to set email alerts
|

A Multidisciplinary Team Approach to the Treatment of Liver Cirrhosis

Abstract: Objective To explore the feasibility of treating cirrhosis using a multidisciplinary team approach (MDT) and to pinpoint the key factors influencing its implementation. Methods The data of 307 patients with decompensated cirrhosis were studied retrospectively. Patients who received more than two treatment measures were assigned to the MDT group (n=228), and patients who received symptomatic medical drug treatment only were assigned to the traditional treatment group (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…A regional, multi-disciplinary approach to the management of end-stage liver disease, LT outreach clinics within large gastroenterology units (jointly run by transplant hepatologists and local gastroenterologists), and ease of communication between referring and LT centres all play a role. 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
“…A regional, multi-disciplinary approach to the management of end-stage liver disease, LT outreach clinics within large gastroenterology units (jointly run by transplant hepatologists and local gastroenterologists), and ease of communication between referring and LT centres all play a role. 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
“…A study by Zhang et al of 307 patients with chronic liver disease patients reported 5-year survival rates to be improved in patients under the care of a multidisciplinary team. 37 A recent study by Singhal et al, using similar dataset from NIS, examined in-hospital mortality of HRS among patients with NASH, alcoholic lever disease (ALD), and chronic viral hepatitis cirrhosis. 9 Their study population had a similar mortality rate as in the current report (25.8%).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Zhang et al . of 307 patients with chronic liver disease patients reported 5‐year survival rates to be improved in patients under the care of a multidisciplinary team 37 …”
Section: Discussionmentioning
confidence: 99%
“…The study group had a significantly higher awareness of major clinical symptoms, diet and use of medication. This improved the activities of daily living and correlated to the QoL [ 63 ]. To facilitate PE, there is the help of technology.…”
Section: Lifestylementioning
confidence: 99%